Prevalence, Evolution, and cis-Regulation of Diel Transcription in Chlamydomonas reinhardtii. Issue 12 (1st December 2014) - Panchy, Nicholas; Wu, Guangxi; Newton, Linsey; Tsai, Chia-Hong; Chen, Jin; Benning, Christoph; Farré, Eva M; Shiu, Shin-Han
Abstract: Endogenous (circadian) and exogenous ( e.g., diel) biological rhythms are a prominent feature of many living systems. In green algal species, knowledge of the extent of diel rhythmicity of genome-wide gene expression, its evolution, and its cis -regulatory mechanism is limited. In this study, we identified cyclically expressed genes under diel conditions in Chlamydomonas reinhardtii and found that 50% of the 17, 114 annotated genes exhibited cyclic expression. These cyclic expression patterns indicate a clear succession of biological processes during the course of a day. Among 237 functional categories enriched in cyclically expressed genes, >90% were phase-specific, including photosynthesis, cell division, and motility-related processes. By contrasting cyclic expression between C. reinhardtii and Arabidopsis thaliana putative orthologs, we found significant but weak conservation in cyclic gene expression patterns. On the other hand, within C. reinhardtii cyclic expression was preferentially maintained between duplicates, and the evolution of phase between paralogs is limited to relatively minor time shifts. Finally, to better understand the cis regulatory basis of diel expression, putative cis -regulatory elements were identified that could predict the expression phase of a subset of the cyclic transcriptome. Our findings demonstrate both the prevalence of cycling genes as well as the complex regulatory circuitry required to control cyclic expression in a green algal model, highlighting the need to consider diel expression in studying algal molecular networks and in future biotechnological applications.